Aluminum paste for topcon cell silver grid and preparation method, composite grid line

By optimizing the aluminum paste composition and particle size distribution, the problem of diffusion alloying of aluminum paste with silver and silicon substrates during high-temperature sintering was solved, achieving high efficiency, cost reduction, and long-term reliability of TOPCon batteries, and improving the open-circuit voltage and photoelectric conversion efficiency of the batteries.

CN122738993BActive Publication Date: 2026-11-06NANTONG T SUN NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611217893.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-11-06
Estimated Expiration
2046-08-12

AI Technical Summary

Technical Problem

Existing aluminum paste diffuses and alloys with silver and silicon substrates during high-temperature sintering, damaging the tunneling oxide passivation layer, leading to a surge in interfacial recombination and a spike in contact resistance, which cannot meet the high-efficiency, cost-reduction, and efficiency-enhancing requirements of TOPCon batteries.

Method used

An aluminum paste composed of aluminum powder, glass powder, organic resin, solvent and nickel-silicon composite barrier agent is formed by optimizing the particle size distribution and glass composition to form a low-diffusion and low-composite aluminum paste, which inhibits silver-aluminum interdiffusion, protects the tunneling oxide passivation layer and improves ohmic contact performance.

Benefits of technology

It significantly reduces interface minority carrier recombination loss, improves battery open-circuit voltage and photoelectric conversion efficiency, ensures strong electrode adhesion and excellent solderability, is compatible with mass production processes, and achieves efficient silver reduction and long-term reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122738993B_ABST
    Figure CN122738993B_ABST
Patent Text Reader

Abstract

The present disclosure provides an aluminum paste for a TOPcon cell silver grid, a preparation method and a composite grid line, and belongs to the technical field of solar cells. The aluminum paste comprises: 75-88 parts by mass of aluminum powder; 1-8 parts by mass of glass powder; 1-5 parts by mass of organic resin; 15-20 parts by mass of solvent; and 0.5-2.5 parts by mass of inorganic additive; wherein the inorganic additive is a nickel-silicon composite barrier additive. The aluminum paste formed by the present disclosure can effectively inhibit the silver-aluminum interdiffusion and alloying reaction in the high-temperature sintering stage, avoid damage to the tunneling oxide passivation layer, significantly reduce the interface minority carrier recombination loss, and greatly improve the open-circuit voltage and photoelectric conversion efficiency of the cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of solar cell technology, specifically relating to an aluminum paste for silver grids in TOPcon cells, a method for its preparation, and composite grid lines. Background Technology

[0002] The photovoltaic industry is currently undergoing a comprehensive upgrade to N-type TOPCon cells. However, the high price and scarcity of silver, coupled with the significant proportion of silver paste in cell costs, make aluminum substitution for silver a core necessity for cost reduction. While silver grid metallization on the back of TOPCon cells offers excellent contact performance, the scarcity and high cost of silver severely restrict the profitability of the industry chain. Conventional aluminum paste, during high-temperature sintering, is prone to excessive interdiffusion alloying with silver and silicon, breaking down the tunneling oxide passivation layer. This results in a surge in interface recombination, a spike in contact resistance, and a significant decrease in cell efficiency and reliability, making it unsuitable for direct overlay printing to adapt to silver grid structures. Furthermore, traditional overlay printing processes suffer from poor interface bonding, uneven thermal matching, and insufficient solderability, making them difficult to integrate with existing screen printing production lines. Therefore, developing a low-diffusion, low-recombination, and highly stable aluminum paste specifically designed for TOPCon silver grid overlay printing, suppressing silver-aluminum-silicon interface degradation while maintaining low contact resistance and passivation protection, and achieving efficient silver reduction and compatibility with mass production processes, holds significant engineering value and industrial importance for cost reduction, efficiency improvement, and long-term large-scale development of TOPCon cells.

[0003] Currently, high-purity silver paste is commonly used to prepare the grid electrodes for the back metallization of N-type TOPCon solar cells. Silver electrodes possess excellent conductivity and ohmic contact performance with the silicon substrate, effectively ensuring the photoelectric conversion efficiency of the cell. However, the precious metal silver is a limited resource with significant price fluctuations, resulting in high production costs for silver paste and substantial compression of the overall profit margin of photovoltaic cells. Therefore, silver-aluminum overprinting composite metallization technology has become the mainstream development direction for cost reduction in the industry.

[0004] Currently, most commercially available aluminum pastes are compatible with traditional P-type PERC cell processes, but they exhibit significant technical limitations when applied to TOPCon silver grid stacking scenarios. For example, during high-temperature sintering, aluminum readily undergoes interdiffusion alloying reactions with silver grid lines and the silicon substrate, forming high-resistivity intermetallic compounds. This disrupts the structural integrity of the tunneling oxide passivation layer, increases the minority carrier recombination rate, and results in a significant decrease in cell open-circuit voltage, fill factor, and photoelectric efficiency.

[0005] Meanwhile, the thermal expansion coefficient of the glass binder phase used in traditional aluminum pastes is poorly matched with that of silver and silicon materials, easily generating significant internal stress after sintering and cooling, leading to problems such as grid line cracking, delamination, and insufficient interfacial bonding. Secondly, existing modified aluminum pastes mostly only optimize the glass composition, resulting in poor silver-aluminum interfacial compatibility. Their weldability and high-temperature aging resistance cannot meet the requirements for long-term outdoor service of photovoltaic modules, making them difficult to adapt to the large-scale screen printing mass production process of TOPCon cells. Overall, their electrical performance and reliability are insufficient to meet practical application standards.

[0006] In summary, existing technologies generally suffer from the following problems: Existing aluminum pastes adapted for TOPCon silver grids exhibit significant interdiffusion between silver and aluminum during high-temperature sintering, forming a high-resistivity alloy phase. This damages the tunneling oxide passivation layer, exacerbates minority carrier recombination at the interface, and results in low open-circuit voltage and severe degradation of photoelectric conversion efficiency. Furthermore, traditional glass systems have poor thermal expansion compatibility with silver and silicon substrates, leading to warping, cracking, and delamination of the grid lines after sintering. The electrode interface bonding strength is insufficient, resulting in poor weldability.

[0007] Secondly, conventional aluminum pastes result in poor wetting and bonding at the silver-aluminum interface, leading to poor interface stability under high-temperature, long-term operating conditions and significant battery aging and thermal cycling degradation. Furthermore, existing aluminum pastes cannot simultaneously achieve low contact resistance, low interface diffusion, high adhesion strength, and compatibility with mass production printing, making it difficult to simultaneously achieve cost reduction and efficiency improvement, high power generation efficiency, and long-term outdoor reliability. This fails to meet the requirements of large-scale mass production of TOPCon batteries and the long-term use of high-reliability modules. Summary of the Invention

[0008] This disclosure aims to at least solve one of the technical problems existing in the prior art, and to provide an aluminum paste for silver grids of TOPcon batteries, a method for preparing the paste, and composite grid lines.

[0009] In one aspect, this disclosure provides an aluminum paste for use on the silver grid of a TOPCon battery, the aluminum paste comprising: 75-88 parts by weight of aluminum powder; 1-8 parts by weight of glass powder; 1-5 parts by weight of organic resin; 15-20 parts by weight of solvent; 0.5-2.5 parts by weight of inorganic additives; wherein, The inorganic additive is a nickel-silicon composite barrier agent.

[0010] Optionally, the nickel-silicon composite barrier agent is a nickel-silicon alloy.

[0011] Optionally, the D50 of the nickel-silicon alloy is 0.5-2.0 μm.

[0012] Optionally, the aluminum powder comprises coarse aluminum powder and fine aluminum powder in a ratio of (3-7):(2-3); wherein, The D50 of the coarse aluminum powder is 3-8 μm; The D50 of the fine aluminum powder is 0.8–2 μm.

[0013] Optionally, the glass powder includes low softening point bismuth-based glass powder and high softening point vanadium-barium-based glass powder in a ratio of (1-2):(9-10).

[0014] Optionally, the low softening point bismuth-based glass powder comprises: 45-55 parts by weight of Bi2O3; 5-15 parts by weight of SiO2; 10-30 parts by weight of ZnO; 5-15 parts by weight of B2O3; 0.1-5 parts by weight of CaCO3; 0.1-5 parts by mass of Al2O3.

[0015] Optionally, the high softening point vanadium-barium glass powder comprises: 30-40 parts by weight of V2O5; 25-35 parts by weight of BaCO3; 10-30 parts by weight of B2O3; 15-25 parts by weight of SiO2; 5-15 parts by weight of P2O5; 0.1-5 parts by weight of SrO; 0.1-5 parts by weight of WO3.

[0016] Optionally, the organic resin includes ethyl cellulose, acrylic resin, and cellulose acetate butyrate.

[0017] Optionally, the solvent includes one or more of terpineol, dodecyl alcohol ester, diethylene glycol butyl ether acetate, and diethylene glycol dibutyl ether.

[0018] In another aspect, this disclosure provides a method for preparing aluminum paste, the method comprising: An organic carrier is prepared by mixing organic resin with solvent. Aluminum powder, glass powder, inorganic additives and a portion of the organic carrier are then mixed evenly and subjected to high-speed dispersion to obtain a mixture. The mixture is fed into a three-roll mill for grinding. During the grinding process, the remaining organic carrier is gradually added until the slurry viscosity reaches the preset standard. Vacuum degassing removes air bubbles from the slurry, and after filtration, a finished aluminum slurry with a fineness of ≤8μm is finally obtained.

[0019] In another aspect of this disclosure, a composite grid line is proposed, the composite grid line comprising a silver grid line and an aluminum grid line overlaid on the silver grid line, the aluminum grid line being formed by sintering the aluminum paste described above.

[0020] This disclosure discloses an aluminum paste for silver grids in TOPCon batteries, its preparation method, and composite grid lines. The aluminum paste comprises: 75-88 parts by weight of aluminum powder; 1-8 parts by weight of glass powder; 1-5 parts by weight of organic resin; 15-20 parts by weight of solvent; and 0.5-2.5 parts by weight of inorganic additives; wherein the inorganic additives are nickel-silicon composite barrier agents. By optimizing the particle size distribution of aluminum powder, customizing low-diffusion bismuth-based and vanadium-barium-based glass binder phases, and composite barrier doping components, the aluminum paste formed effectively suppresses silver-aluminum interdiffusion and alloying reactions during high-temperature sintering, avoids damage to the tunneling oxide passivation layer, significantly reduces interfacial minority carrier recombination losses, and greatly improves the open-circuit voltage and photoelectric conversion efficiency of the battery. Attached Figure Description

[0021] Figure 1 This is a flowchart illustrating the aluminum paste preparation method according to a specific embodiment of this disclosure. Detailed Implementation

[0022] To enable those skilled in the art to better understand the technical solutions of this disclosure, the disclosure will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this disclosure and represent a part of the embodiments of this disclosure, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without creative effort are within the protection scope of this disclosure.

[0023] In one aspect of this disclosure, an aluminum paste for silver grids in TOPCon batteries is provided, the aluminum paste comprising: 75-88 parts by weight of aluminum powder; 1-8 parts by weight of glass powder; 1-5 parts by weight of organic resin; 15-20 parts by weight of solvent; and 0.5-2.5 parts by weight of inorganic additives; wherein the inorganic additives are nickel-silicon composite barrier agents.

[0024] In this embodiment, when aluminum paste formed by doping aluminum powder, glass powder and other components with composite barrier agent is overprinted on the silver grid of TOPCon battery, it can effectively suppress the silver-aluminum interdiffusion and alloying reaction during the high-temperature sintering stage, avoid damage to the tunneling oxide passivation layer, significantly reduce the interface minority carrier recombination loss, and greatly improve the battery open-circuit voltage and photoelectric conversion efficiency.

[0025] In some preferred embodiments, the aluminum powder comprises coarse aluminum powder and fine aluminum powder in a ratio of 7:3, wherein the D50 of the coarse aluminum powder is 3-8 μm; the D50 of the fine aluminum powder is 0.8-2 μm, and the purity of the aluminum powder is ≥99.99% and the oxygen content is ≤0.35%.

[0026] This embodiment utilizes coarse-fine bimodal spherical composite aluminum powder. Large particles form the conductive framework, while small particles fill the interparticle gaps, significantly improving powder packing density and forming a continuous, dense conductive network. This effectively reduces electrode series resistance, optimizes ohmic contact, and enhances battery fill factor and photoelectric conversion efficiency. Compared to traditional flake aluminum powder, spherical aluminum powder has a regular surface and mild high-temperature diffusion activity, effectively slowing silver-aluminum interdiffusion, inhibiting the formation of high-resistivity brittle alloy phases, protecting the TOPCon tunneling oxide passivation layer, reducing minority carrier interface recombination, and stabilizing open-circuit voltage. Simultaneously, the spherical particles exhibit uniform sintering shrinkage and excellent thermal stress matching, reducing the likelihood of grid line cracking, delamination, and electrode adhesion, resulting in excellent solderability. The slurry exhibits excellent thixotropy and printability, making it suitable for high-speed screen printing processes in mass production. It also demonstrates good stability under humid heat and thermal cycling, good powder oxidation resistance, and resistance to clumping during storage. Batch performance is stable, facilitating large-scale mass production applications.

[0027] In some other preferred embodiments, the glass powder comprises low softening point bismuth-based glass powder and high softening point vanadium-barium-based glass powder in a ratio of (1-2):(9-10).

[0028] As a further preferred embodiment, the low softening point bismuth-based glass powder comprises: 45-55 parts by mass of Bi2O3; 5-15 parts by mass of SiO2; 10-30 parts by mass of ZnO; 5-15 parts by mass of B2O3; 0.1-5 parts by mass of CaCO3; and 0.1-5 parts by mass of Al2O3.

[0029] In this embodiment, the components of the low-softening-point bismuth-based glass powder work synergistically to meet the low-temperature sintering requirements of TOPCon silver grid overprinted aluminum paste, taking into account adhesion, barrier properties, and interface protection. Specifically, Bi₂O₃, as the low-melting-point main component, lowers the glass softening point to 380–450°C, enabling rapid low-temperature melting and spreading to encapsulate the aluminum powder, improving interface wettability and ohmic contact without corroding the tunneling oxide layer; SiO₂ constructs the glass network framework, enhancing structural stability and mechanical strength, fine-tuning the coefficient of thermal expansion to match the silicon and silver substrates, alleviating sintering stress, and preventing grid line cracking and detachment; ZnO lowers the glass softening temperature and melt viscosity, optimizing fluidity and formability, improving compatibility with aluminum powder and silver grids, and helping to suppress initial aluminum atom diffusion; B₂O₃ further lowers the softening point and promotes low-temperature melting, adapting to mass production processes, while improving glass thermal stability and continuity, and initially blocking slight diffusion of silver and aluminum atoms; small amounts of CaCO₃ and Al₂O₃ precisely control the coefficient of thermal expansion, improving thermal matching, enhancing the glass's resistance to damp heat and mechanical strength, and ensuring long-term electrode reliability.

[0030] As a further preferred option, the high softening point vanadium-barium glass powder comprises: 30-40 parts by mass of V2O5; 25-35 parts by mass of BaCO3; 10-30 parts by mass of B2O3; 15-25 parts by mass of SiO2; 5-15 parts by mass of P2O5; 0.1-5 parts by mass of SrO; and 0.1-5 parts by mass of WO3.

[0031] In this embodiment, V₂O₅ can raise the glass softening point to 520–600°C, forming a dense barrier film at high temperatures to block the interdiffusion of silver and aluminum atoms, inhibit the formation of high-resistivity alloy phases, protect the tunneling layer, and stabilize the open-circuit voltage. BaO enhances the high-temperature thermal and chemical stability of the glass, adjusts the coefficient of thermal expansion to match the silver and aluminum electrodes, alleviates thermal stress, and enhances the electrode's weldability and resistance to thermal cycling. SiO₂ constructs a stable glass network, improves mechanical strength and high-temperature resistance, enhances the bonding force with the silver-aluminum interface, ensures long-term barrier effect, and optimizes electrical performance. P₂O₅ optimizes the glass melting characteristics, ensures the density of the barrier film, improves resistance to damp heat aging, and reduces battery power decay. A small amount of SrO and WO₃ fine-tunes the glass crystal phase structure, improves high-temperature stability and barrier performance, enhances oxidation resistance and interfacial compatibility, and comprehensively improves the overall performance of the electrode.

[0032] In this embodiment, the aforementioned high softening point vanadium-barium glass powder and bismuth-based glass work together to provide high-temperature barrier and suppress silver-aluminum interdiffusion, thus meeting the long-term service requirements of overprinted electrodes.

[0033] In some other preferred embodiments, the nickel-silicon composite barrier agent is a nickel-silicon alloy with a particle size D50 controlled between 0.5 and 2.0 μm.

[0034] In this embodiment, the aforementioned nickel-silicon composite barrier agent exhibits excellent compatibility with the aluminum paste system, can be uniformly dispersed in the aluminum powder and organic carrier, and does not chemically react with other components. Furthermore, the main form of the aforementioned nickel-silicon composite barrier agent is ultrafine nickel-silicon alloy powder, which can fully integrate with other components in the aluminum paste (such as glass powder and organic binders) without significant agglomeration. It is suitable for the mixing and printing processes of TOPCon aluminum paste and meets the purity requirements of photovoltaic aluminum paste, with impurity content (Fe, Cu, Si, etc.) ≤0.1%, thus not negatively impacting battery performance.

[0035] In other preferred embodiments, the organic resin includes ethyl cellulose, acrylic resin, and cellulose acetate butyrate.

[0036] As a further preferred option, the content ratio of ethyl cellulose, acrylic resin and cellulose acetate butyrate is 3:(1-2):(1-2).

[0037] In other preferred embodiments, the solvent includes one or more of terpineol, dodecyl alcohol ester, diethylene glycol butyl ether acetate, and diethylene glycol dibutyl ether.

[0038] As a further preferred option, the solvent is preferably a dodecayl alcohol ester and diethylene glycol butyl ether acetate in a volume ratio of (1-2):(3-5).

[0039] As shown in Figure 1, another aspect of this disclosure provides a method for preparing aluminum paste, S100, which specifically includes the following steps S110 to S130: S110. Organic resin and solvent are mixed to form an organic carrier. Aluminum powder, glass powder, inorganic additives and a portion of the organic carrier are then mixed evenly and subjected to high-speed dispersion treatment to ensure that the metal powder is fully impregnated, resulting in a mixture.

[0040] In step S110, the content of aluminum powder is 75-88 parts by mass, for example, preferably 75 parts by mass, 78 parts by mass, 80 parts by mass, 83 parts by mass, 88 parts by mass, etc.

[0041] In step S110, the content of glass powder is 1-8 parts by mass, for example, preferably 1 part by mass, 3 parts by mass, 5 parts by mass, 7 parts by mass, 8 parts by mass, etc.

[0042] In step S110, the content of the inorganic additive is 0.5-2.5 parts by mass, for example, preferably 0.5 parts by mass, 1 part by mass, 1.5 parts by mass, etc.

[0043] In step S110, the content of organic resin is 1-5 parts by mass, for example, preferably 1 part by mass, 3 parts by mass, 5 parts by mass, etc.

[0044] In step S110, the solvent content is 15-20 parts by mass, for example, preferably 15 parts by mass, 20 parts by mass, etc.

[0045] It should be noted that the content of the organic carrier here is preferably 16-25 parts by mass, and its concentration is 65-75%.

[0046] S120. The mixture is fed into a three-roll mill for grinding. After three rounds of fine grinding, the remaining organic carrier is gradually added during the grinding process until the viscosity of the slurry reaches the preset standard.

[0047] S130. Vacuum degassing removes air bubbles from the slurry, and after filtration, a finished aluminum slurry with a fineness ≤8μm is finally obtained.

[0048] In another aspect of this disclosure, a composite grid line is proposed, the composite grid line comprising a silver grid line and an aluminum grid line overlaid on the silver grid line, the aluminum grid line being formed by sintering the aluminum paste described above.

[0049] The aluminum paste formed by this disclosure can be used for silver-aluminum overprinted grid line electrodes on the back of N-type TOPCon batteries. The aluminum paste is printed on a silver base layer, and after drying and sintering, a composite grid line is formed, which forms a continuous conductive path with the underlying silver grid, efficiently collecting and transmitting photocurrent and reducing electrode series resistance.

[0050] The following will further illustrate the aluminum paste overprinted on the silver grid of the TOPCon battery and its performance with specific embodiments: Example 1 Under normal temperature and dry conditions, 75 parts by weight of mixed aluminum powder, 2 parts by weight of glass powder, 2 parts by weight of inorganic additives, and 21 parts by weight of organic carrier with a concentration of 70% (the organic carrier includes 14.7 parts by weight of organic resin and 6.3 parts by weight of solvent) are mixed evenly and then subjected to high-speed dispersion treatment to ensure that the metal powder is fully wetted. Then, the mixture is fed into a three-roll mill and subjected to three fine grinding processes. During the grinding process, the remaining organic carrier is gradually added until the viscosity of the slurry reaches the preset standard. Finally, the air bubbles inside the slurry are removed by vacuum degassing and filtered to obtain a finished aluminum slurry with a fineness of ≤8μm and excellent thixotropic properties.

[0051] Please refer to Table 1 for the relevant components and contents of aluminum powder, glass powder, inorganic additives, organic resin, and solvent. The aluminum powder used is coarse aluminum powder with a single particle size of D50-6-7μm. The nickel-silicon composite barrier agent is a nickel-silicon alloy, model Ni2Si, with a purity ≥99%.

[0052] Example 2 The aluminum paste preparation process in Example 2 is the same as in Example 1. Please refer to Table 1 for the relevant components and contents of aluminum powder, glass powder, inorganic additives, organic resin, and solvent.

[0053] The aluminum powder used is a blend of coarse aluminum powders with different particle sizes. Coarse aluminum powder 1 has a D50 of 6-7 μm, and coarse aluminum powder 2 has a D50 of 7-8 μm. The ratio of coarse aluminum powder 1 to coarse aluminum powder 2 is 3:2. The nickel-silicon composite barrier agent is of type Ni2Si with a purity ≥99%.

[0054] Example 3 The aluminum paste preparation process in Example 3 is the same as in Example 1. Please refer to Table 1 for the relevant components and contents of aluminum powder, glass powder, inorganic additives, organic resin, and solvent.

[0055] Among them, the ratio of low softening point bismuth-based glass powder to high softening point vanadium-barium-based glass powder in the glass powder is 1:10, and the nickel-silicon composite barrier additive is Ni2Si with a purity of ≥99%.

[0056] Secondly, the aluminum powder is a blend of coarse aluminum powders with different particle sizes. The D50 of coarse aluminum powder 1 is 6-7 μm, and the D50 of coarse aluminum powder 2 is 7-8 μm. The content ratio of coarse aluminum powder 1 to coarse aluminum powder 2 is 3:2.

[0057] Example 4 The aluminum paste preparation process in Example 4 is the same as in Example 1. Please refer to Table 1 for the relevant components and contents of aluminum powder, glass powder, inorganic additives, organic resin, and solvent. Specifically, the ratio of low-softening-point bismuth-based glass powder to high-softening-point vanadium-barium-based glass powder in the glass powder is 1:10. The nickel-silicon composite barrier agent is of type Ni2Si with a purity ≥99%.

[0058] Secondly, the aluminum powder is a blend of coarse and fine aluminum powder with different particle sizes. The D50 of the coarse aluminum powder is 6-7μm, and the D50 of the fine aluminum powder is 2-3μm. The ratio of coarse to fine aluminum powder is 7:3.

[0059] Example 5 For the aluminum powder, glass powder, inorganic additives, organic resin, solvent, and related components and contents of the inorganic additives in Example 5, please refer to Table 1. Specifically, the ratio of low softening point bismuth-based glass powder to high softening point vanadium-barium-based glass powder in the glass powder is 1:10, and the nickel-silicon composite barrier agent is of type Ni2Si with a purity ≥99%.

[0060] Secondly, the aluminum powder is a blend of coarse and fine aluminum powder with different particle sizes. The D50 of the coarse aluminum powder is 6-7μm, and the D50 of the fine aluminum powder is 2-3μm. The ratio of coarse to fine aluminum powder is 7:3.

[0061] Comparative Example 1 Under normal temperature and dry conditions, 77 parts by weight of mixed aluminum powder, 2 parts by weight of glass powder, and 21 parts by weight of 70% organic carrier (which includes 14.7 parts by weight of organic resin and 6.3 parts by weight of solvent) are mixed evenly and then subjected to high-speed dispersion to ensure that the metal powder is fully wetted. The mixture is then fed into a three-roll mill and finely ground in three stages. During the grinding process, the remaining organic carrier is gradually added until the viscosity of the slurry reaches the preset standard. Finally, the air bubbles inside the slurry are removed by vacuum degassing and filtered to obtain a finished aluminum slurry with a fineness of ≤8μm and excellent thixotropic properties.

[0062] Please refer to Table 1 for the relevant components and contents of aluminum powder, glass powder, organic resin, and solvent in Comparative Example 1.

[0063] Comparative Example 2 The aluminum paste preparation process of Comparative Example 2 is the same as that of Comparative Example 1. Please refer to Table 1 for the relevant components and contents of aluminum powder, glass powder, organic resin, and solvent.

[0064] The aluminum powder used is a blend of coarse aluminum powders with different particle sizes. The D50 of coarse aluminum powder 1 is 6-7 μm, the D50 of coarse aluminum powder 2 is 7-8 μm, and the content ratio of coarse aluminum powder 1 to coarse aluminum powder 2 is 3:2.

[0065] Table 1. Aluminum paste formulations for each embodiment and comparative example.

[0066] Furthermore, the aluminum paste from the above embodiments and comparative examples was printed onto the silver grid of the TOPCon battery and sintered to form a gate electrode structure. The results of its open-circuit voltage, short-circuit current, PL recombination value, fill factor, and photoelectric efficiency are shown in Table 2 below.

[0067] Table 2 Test results for each embodiment and comparative example

[0068] According to the results in Tables 1 and 2 above, Comparative Example 1, which uses aluminum powder of a single particle size and bismuth-based glass powder, has the worst overall performance, with Voc=0.7V, a conversion efficiency of 25.1%, and the lowest minority carrier recombination value in the PL test. This indicates that the single-particle-size aluminum powder has a low packing density and a high electrode series resistance. At the same time, the single bismuth-based glass powder cannot block the bidirectional interdiffusion of silver and aluminum atoms during high-temperature sintering, which will seriously damage the tunneling oxide passivation layer of the TOPCon cell and ultimately cause a significant increase in the minority carrier recombination rate at the silicon wafer interface. Secondly, according to Comparative Example 2 and Example 2, when a nickel-silicon composite barrier agent is introduced into aluminum powder of the same particle size and a single glass system, the minority carrier recombination value in the PL test increases. This indicates that the nickel-silicon composite barrier agent can independently play a role in blocking high-temperature metal diffusion, making up for the deficiency of the single bismuth-based glass powder in suppressing silver-aluminum interdiffusion. At the same time, the agent has excellent compatibility with the bimodal aluminum paste system, reducing interface minority carrier recombination defects without damaging the electrode conductive network, and improving the battery passivation performance, open-circuit voltage and photoelectric conversion efficiency.

[0069] In summary, based on Comparative Examples 1 and 2 and Examples 1-5, it can be seen that the bimodal spherical aluminum powder composite of coarse and fine aluminum powder can increase the powder packing density and form a denser conductive network. This reduces electrode series resistance and minimizes composite defects caused by interfacial porosity, resulting in a stable gain on battery efficiency and passivation effect. Furthermore, based on Comparative Example 2 and Examples 1-5, it can be seen that bismuth-based glass powder alone cannot suppress silver-aluminum interdiffusion and will still damage the passivation contact structure of TOPCon. However, the bismuth-based (low softening point wetting) + vanadium-based (high softening point barrier) composite glass powder combined with nickel-silicon composite barrier additives can achieve a synergistic effect of low-temperature wetting of aluminum powder and high-temperature barrier to metal diffusion, thereby reducing passivation layer damage at the source.

[0070] In summary, based on the above test results, the following conclusions can be drawn: 1. Compared with single-particle-size aluminum powder, bimodal composite spherical aluminum powder has a denser packing and a more continuous conductive network, which can significantly improve open-circuit voltage and battery conversion efficiency, reduce minority carrier recombination loss, and its overall electrical performance is significantly better than that of single-particle-size aluminum paste formulation.

[0071] 2. Both bismuth-based and vanadium-barium-based glass have their shortcomings when used alone. However, when the two glass powders are used in combination, they can firmly bond the electrodes at low temperatures and effectively block the interdiffusion of silver and aluminum, significantly improving Voc and suppressing interfacial recombination. The battery efficiency improvement effect is far superior to that of a single glass system.

[0072] 3. The combination of aluminum powders with different particle sizes, along with the optimized resin and solvent ratio, can improve printing and sintering characteristics, further increase the filler factor, and significantly improve the photoelectric conversion efficiency of the battery.

[0073] 4. After adding nickel-silicon composite barrier inorganic additives, interfacial diffusion is effectively suppressed, minority carrier recombination is further reduced, the open circuit voltage reaches the optimal level, the PL recombination value is significantly improved, and the battery photoelectric conversion efficiency can reach up to 27.05%.

[0074] 5. This disclosure uses bimodal particle size aluminum powder, high and low temperature composite glass, nickel-silicon barrier additives and optimized organic system formulation, which is superior to traditional comparative formulations in terms of open circuit voltage, minority carrier recombination, fill factor and power generation efficiency. It is also compatible with TOPCon silver grid overprinting process and has significant performance advantages.

[0075] It is understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of this disclosure, and this disclosure is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and substance of this disclosure, and these modifications and improvements are also considered to be within the scope of protection of this disclosure.

Claims

1. An aluminum paste for silver grids in TOPcon batteries, characterized in that, The aluminum paste includes: 75-88 parts by weight of aluminum powder; 1-8 parts by weight of glass powder; 1-5 parts by weight of organic resin; 15-20 parts by weight of solvent; 0.5-2.5 parts by weight of inorganic additives; wherein, The inorganic additive is a nickel-silicon composite barrier agent; The glass powder comprises low softening point bismuth-based glass powder and high softening point vanadium-barium-based glass powder in a ratio of (1-2):(9-10). The low softening point bismuth-based glass powder includes: 45-55 parts by weight of Bi2O3; 5-15 parts by weight of SiO2; 10-30 parts by weight of ZnO; 5-15 parts by weight of B2O3; 0.1-5 parts by mass of CaCO3; 0.1-5 parts by mass of Al2O3; The high softening point vanadium-barium glass powder comprises: 30-40 parts by weight of V2O5; 25-35 parts by weight of BaCO3; 10-30 parts by weight of B2O3; 15-25 parts by weight of SiO2; 5-15 parts by weight of P2O5; 0.1-5 parts by weight of SrO; 0.1-5 parts by weight of WO3.

2. The aluminum paste according to claim 1, characterized in that, The nickel-silicon composite barrier agent is a nickel-silicon alloy.

3. The aluminum paste according to claim 2, characterized in that, The D50 of the nickel-silicon alloy is 0.5-2.0 μm.

4. The aluminum paste according to claim 1, characterized in that, The aluminum powder comprises coarse aluminum powder and fine aluminum powder in a ratio of (3-7):(2-3); wherein, The D50 of the coarse aluminum powder is 3-8 μm; The D50 of the fine aluminum powder is 0.8–2 μm.

5. The aluminum paste according to claim 1, characterized in that, The organic resins include ethyl cellulose, acrylic resin, and cellulose acetate butyrate; The solvent includes one or more of terpineol, dodecyl alcohol ester, diethylene glycol butyl ether acetate, and diethylene glycol dibutyl ether.

6. A method for preparing the aluminum paste according to any one of claims 1-5, characterized in that, The method includes: An organic carrier is prepared by mixing organic resin with solvent. Aluminum powder, glass powder, inorganic additives and a portion of the organic carrier are then mixed evenly and subjected to high-speed dispersion to obtain a mixture. The mixture is fed into a three-roll mill for grinding. During the grinding process, the remaining organic carrier is gradually added until the slurry viscosity reaches the preset standard. Vacuum degassing removes air bubbles from the slurry, and after filtration, a finished aluminum slurry with a fineness of ≤8μm is finally obtained.

7. A composite grid line, characterized in that, The composite grid line includes a silver grid line and an aluminum grid line overlaid on the silver grid line, wherein the aluminum grid line is formed by sintering the aluminum paste according to any one of claims 1-5.

Citation Information

Patent Citations

  • Base metal conductive paste for TOPCon battery and preparation method and application of base metal conductive paste

    CN121938688A

  • Photovoltaic TOPCon aluminum paste and preparation method and application thereof

    CN122552225A